Biogeomorphology, terrestrial and freshwater systems : proceedings of the 26th Binghamton Symposium in Geomorphology, held October 6-8, 1995 - Hupp, C. R.; Osterkamp, W. R.; Howard, Alan D. (Elsevier, 1995)
Biogeomorphology, a relatively new term, refers to relations between the biota and geomorphic form and process. Ecology is the study of organisms in relation to their physical and biotic environment. Thus, ecogeomorphology could have been an equally acceptable name for this publication which stresses the ecological aspects of the larger field of biology. Most of the articles relate vegetation to fluvial geomorphology, erosion, and sedimentation. However, articles showing the significance of animal ecological studies and their bearing on geomorphic form and process are also included. Geographically the papers range from arid areas in the American Southwest and Israel to the new world tropics. Most articles, however, are concerned with temperate areas of North America and Western Europe. This is among the first books to approach the role that biota and ecology play in geomorphic processes and should be on the shelf of every landscape ecologist.